2011
DOI: 10.1093/cvr/cvr319
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of natriuretic peptide receptor-A enhances receptor C expression and signalling in vascular smooth muscle cells

Abstract: These results demonstrate that knockdown of NPR-A up-regulates the expression of NPR-C, Giα proteins, and NPR-C-linked AC signalling and suggests a cross-talk between NPR-A and NPR-C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…As the mammalian heart is composed of a heterogeneous mixture of different cell types it will be necessary to determine how the endogenous production of cardiac natriuretic peptides and their receptors regulate the proliferation of these distinctive cell types during cardiogenesis in vivo. In addition, it was shown in mammalian smooth muscle cells that knockdown of Npr1 increased the expression of Npr3, which suggests that cellular pathways exist that regulate the coordinated expression of these receptors (Li et al, 2012). We did not see the same coordinated regulation of Npr1 and Npr3 expression in our in vivo zebrafish model system, but we did see potential feedback regulation of nppa/nppb transcription in our targeted knockdown models.…”
Section: Research Articlementioning
confidence: 60%
“…As the mammalian heart is composed of a heterogeneous mixture of different cell types it will be necessary to determine how the endogenous production of cardiac natriuretic peptides and their receptors regulate the proliferation of these distinctive cell types during cardiogenesis in vivo. In addition, it was shown in mammalian smooth muscle cells that knockdown of Npr1 increased the expression of Npr3, which suggests that cellular pathways exist that regulate the coordinated expression of these receptors (Li et al, 2012). We did not see the same coordinated regulation of Npr1 and Npr3 expression in our in vivo zebrafish model system, but we did see potential feedback regulation of nppa/nppb transcription in our targeted knockdown models.…”
Section: Research Articlementioning
confidence: 60%
“…Li et al. showed that knockdown of NPR-A leads to upregulation of NPR-C mRNA in vascular smooth muscle cells [56] . However, we did not see any changes in NPR-A mRNA levels with and without treatment on ND or HFD.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Dosage of the 8-Br-cGMP was based on studies from other groups 29 , 30 as well as reports which revealed that only a small fraction of exogenously added 8-Br-cGMP is detectable in the cytoplasm 31 . The addition of 8-Br-cGMP at 10 µM and 100 µM significantly increased the gene expression of HCN4 (3.4-fold and 5.3-fold respectively Vs. control, P < 0.005, Fig.…”
Section: Resultsmentioning
confidence: 99%